Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Selected Regular Lectures From the 12th International Congress on Mathematical Education 2015
DOI: 10.1007/978-3-319-17187-6_27
|View full text |Cite
|
Sign up to set email alerts
|

Riding the Third Wave: Negotiating Teacher and Students’ Value Preferences Relating to Effective Mathematics Lesson

Abstract: The "Third Wave" is an ongoing international collaborative mathematics education research project, involving 10 countries conducted over the years [2009][2010][2011]. Adopting the theoretical framework of social cultural perspective, the project aimed to explore the contextually-bound understanding and meaning of what counts as effective mathematics lesson from both the teachers and pupils' perspectives. This paper will begin with a brief description of the Third Wave Study Project, the research framework and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 11 publications
(12 reference statements)
1
10
0
Order By: Relevance
“…These responses indicated that students' perceived success and understanding in mathematics was achieved through hard work and practice. The results of the current study with Pāsifika students are broadly consistent with other values research from Europe and Asia (Lee and Seah 2015;Lim 2015;Österling and Andersson 2013) where students were reported to value effort and practice for their mathematics learning. This finding has important implications in challenging ongoing deficit perceptions and low expectations that many New Zealand teachers have towards their Pāsifika students (Rubie-Davies 2009.…”
Section: Effort/practicesupporting
confidence: 89%
See 1 more Smart Citation
“…These responses indicated that students' perceived success and understanding in mathematics was achieved through hard work and practice. The results of the current study with Pāsifika students are broadly consistent with other values research from Europe and Asia (Lee and Seah 2015;Lim 2015;Österling and Andersson 2013) where students were reported to value effort and practice for their mathematics learning. This finding has important implications in challenging ongoing deficit perceptions and low expectations that many New Zealand teachers have towards their Pāsifika students (Rubie-Davies 2009.…”
Section: Effort/practicesupporting
confidence: 89%
“…We discovered that Pāsifika students' valued mathematics which was useful and/or practical for the present or future, and valued effort and practice as important for success in mathematics. The commonality of these two values across international research studies (e.g., Barkatas and Seah 2015;Lee and Seah 2015;Lim 2015;Österling and Andersson 2013) suggests these mathematics educational values are influenced by common societal and educational values.…”
Section: Discussionmentioning
confidence: 99%
“…Evident in the student responses was the perception that to succeed in mathematics requires a personal effort. Earlier studies in different cultural contexts (e.g., Lim, 2015;Ö sterling & Andersson, 2013) have also indicated students' valuing of effort and practice in mathematical learning.…”
Section: Resultsmentioning
confidence: 96%
“…In Hong Kong, junior students considered enjoyment, order, achievement, student involvement, teacher-led monitoring, and teacher support to be vital to the effective learning of mathematics (Law et al 2012). Malaysian primary students valued board work, exercise or practice, learning through mistakes, explanation and students' involvement as the five common elements of an effective mathematics lesson (Lim 2015). In Japan, fifth grade students tended to value process, effort, exploration, fact, openness and progress, whereas ninth grade students tended to value product, ability, exposition, idea, mystery, and control (Shinno et al 2014) suggesting students' values can change over time.…”
Section: Previous Researchmentioning
confidence: 99%